Drag-queens para além de suas performances em Para Wong Foo, obrigado por tudo! - Sousa dos Santos, José Adailton; Newmar, Julie (Revista Inter-Legere, 2018)
Drag-queens para além de suas performances em Para Wong Foo, obrigado por tudo!